Skeletal overgrowth in a pre-pubescent child treated with pan-FGFR inhibitor - Fataneh Majlessipour; Gaohui Zhu; Nicole Baca; Meenasri Kumbaji; Vivian Hwa; Moise Danielpour (Heliyon, 2024)
Fibroblast growth factors and their receptors (FGFR) have major roles in both human growth and oncogenesis. In adults, therapeutic FGFR inhibitors have been successful against tumors that carry somatic FGFR mutations. In pediatric patients, trials testing these anti-tumor FGFR inhibitor therapeutics are underway, with several recent reports suggesting modest positive responses. Herein, we report an unforeseen outcome in a pre-pubescent child with an FGFR1-mutated glioma who was successfully treated with FDA-approved erdafitinib, a pan-FGFR inhibitor approved for treatment of Bladder tumors. While on treatment with erdafitinib, the patient experienced rapid skeletal and long bone overgrowth resulting in kyphoscoliosis, reminiscent of patients with congenital loss-of-function FGFR3 mutations. We utilized normal dermal fibroblast cells established from the patient as a surrogate model to demonstrate that insulin-like growth factor 1 (IGF-1), a factor important for developmental growth of bones and tissues, can activate the PI3K/AKT pathway in erdafitinib-treated cells but not the MAPK/ERK pathway. The IGF-I-activated PI3K/AKT signaling rescued normal fibroblasts from the cytotoxic effects of erdafitinib by promoting cell survival. We, therefore, postulate that IGF-I-activated P13K/AKT signaling likely continues to promote bone elongation in the growing child, but not in adults, treated with therapeutic pan-FGFR inhibitors. Importantly, since activated MAPK signaling counters bone elongation, we further postulate that prolonged blockage of the MAPK pathway with pan-FGFR inhibitors, together with actions of growth-promoting factors including IGF-1, could explain the abnormal skeletal and axial growth suffered by our pre-pubertal patient during systemic therapeutic use of pan-FGFR inhibitors. Further studies to find more targeted, and/or appropriate dosing, of pan-FGFR inhibitor therapeutics for children are essential to avoid unexpected off-target effects as was observed in our young patient.